ANALISIS PERILAKU KOMPLAIN KONSUMEN ONLINE SHOPPING - Aisyiyah, Nasyiatul; Hartoyo, ,; Krisnatuti, Diah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Online business has a strong role to meet consumer need but this business still has limitation so cause increasing of complaint behavior. This study aims to analyze the influence of the quality of online product and service on consumer complaint behavior and its relation with consumer’s personality. The study used cross sectional desaign with online survey. Respondents were 161 college student of 17-22 years old and chosen by purposive sampling based on the criteria of having experienced dissatisfaction in online shopping in the past year. Data were analyzed descriptively and SEM (Structural Equation Modelling) with Smart-PLS software. The result show that consumer dissatisfaction is caused by product defect, delivery time, and product deliver failed. Fashion and cosmetic categories have the highest level of dissatisfaction. Online shopping consumers have various ways to respond to dissatisfaction including passive (34.0%), (voicer 40.0%), iratest (25.0%), and activists (1.0%). Consumer complaint behavior is positively and significantly influenced by perceived quality (product and service) and personality. It means that the higher level of defect in product and service perceived by customers, the higher level of complains that consumers will make. Furthermore, consumer personality characteristics of extraversion and openness to experience are more likely to complaint if there is an error in product or service.